Comparative efficacy of parental and intravaginal administration of PGF2a for the treatment ofpyometra in bitches - PANDEY, NISHI; PRABHAKAR, S; GANDOTRA, V K; NANDA, A S; SINGLA, V K (The Indian Journal of Animal Reproduction, 2023)
A total of fourteen pyometra affected bitches were treated with PGF2cx for a minimum period of 5 days either by subcutaneous route (Group-I; n=S)@ 0.1 mg/kg b.i.d. or by intravaginal route (Group II; n = 6) @ 0.15 o.i.d. ·along with antibiotics. In group I, six bitches (75%) responded to the therapy; 4 in one series while 2 required second series of PGF2cx therapy. In group II all the bitches (I 00%) responded to the treatment. The number of PGF 2cx administration per animal required with intravaginal route was significantly lower (P < 0.05) than with parenteral administration. The side effects were less pronounced by intravaginal route. Successful treatment in both the groups was associated with disappearance of clinical signs of pyometra. It thus appeared that both the routes .of PGFlx administration along with antibiotics were effective to treat pyometra in bitches. However, the intravaginal administration was advantageous, as it required fewer administration and the side effects were milder.